(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Energy is frequently referred to as a country’s backbone. The socioeconomic status of a country can be influenced by energy use and consumption habits. Most industrial and home operations are now performed by equipment that runs on conventional energy as a result of technological advancements. Thermal power plants are responsible for a large portion of India’s conventional electricity. It has two consequences: first, it causes pollution, and secondly, it jeopardises India’s energy sector, as the country imports the great majority of crude oil and coal. One of the most harmful factors is these power plants. India, with the nation’s biggest national grid network, is frequently unable to supply the quantity of energy promised, and the system’s dependability is a cause of worry. Solar PV, on either side, is a long-term energy source that helps to reduce carbon dioxide emissions, despite the fact that it is weather-dependent and sporadic. Solar PV must be built with sufficient storage space to be dependable. In solar technology, a battery bank is typically utilised to store energy. Batteries are not used since they are harmful to the environment if discarded and eaten. In this regard, a technology that combines solar PV with the present grid is discussed in order to provide suitable alternatives for achieving excellent electricity 24 hours a day, seven days a week is detailed. The system is designed to get its electricity from solar PV on bright days, and if there was a power outage, it may be pulled from the grid. The mechanism pumps power into the grid when excess power generation exceeds load demand. The method investigates the impacts of helps produce and attempts to determine the best model size and cost. The programme replicates the model to identify innovative ways to increase integration of renewable energy, reduce power outages, and preserve the quality of electricity provided. The suggested plan lays out some of the most practical and cost-effective strategy for providing a high quality, dependable, and affordable supply of energy for home use.